A REVIEW OF THE EMERGENCE OF INDONESIAN MODERN INTERIOR DESIGN - Santosa, Adi (Dimensi Interior, 2003)
The emergence of Indonesian modern interior design begun by the opening of Liberalism in the Dutch East Indies. The establishment of new private enterprises and immigration of European were the connected factors in entering the modern concepts in interior design. Many schools that had been established since applying of Ethic Politic -especially technical schools - arose Indonesian modern designer pioneers and also arose a specific style of Indonesian modern design: Indo-European Style. The progress of communication technology in the late nineteenth century accelerated the influences of international movements in enriching the development of Indonesian modern interior design.